The Impact of COVID-19 on the Financial Markets, Energy Price and Exchange Rates of GCC Countries - Alalami, Ahlam Khalid; Raheem, Mohamed Mahees; Uluyol, Burhan; Hakim, Shabir (International Journal of Energy Economics and Policy, 2025)
No one denies that the COVID-19 health crisis has substantial impact on the financial markets of the globe. It is important to evaluate the performance of financial assets to understand the behaviour of financial markets during such significant event. Therefore, this research investigates the impact of COVID-19 on the GCC stock indices, currency exchange, and oil returns. By application of the event study (constant return Model) and standard Vector Auto-regression models, we examine the index returns of each country, oil price, and currency exchange before and after COVID-19 health crisis. We find that the COVID-19 has a short-term impact on the index returns of Saudi Arabia, and it has a short-term effect on the exchange returns of all GCC counties except Bahrain. However, the COVID-19 has no long-term impact on all selected variables of GCC. This study provides new insight into the financial market during external event which may have a direct or indirect effect on the performance of selected variables of GCC.